Pengaruh Kompetensi dan Independensi Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderating Study Kasus Auditor BPK Perwakilan KEPRI - Mulyadi Dwi Hariyanto; Faris Ramadhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study investigates the influence of competency and independence against the quality of audit and also examines whether competency and independence moderated by auditor ethics influence the audit quality, remember both of those are important to result in good audit quality. The result indicates that the independent variable competency affected audit quality significantly and the independent variable that independency affected audit quality but not significantly. Besides that, this research found that the interaction between competency and auditor ethics and also the interaction between independence and auditor ethics have a significant effect on the quality of audit. The conclusion obtained is competency, the interaction between competency and ethics, and also the interaction between independence and ethics that influence the audit quality significantly. and independent variable that independency effected audit quality but not significantly, For future research expected can use other moderating variables influencing independence, competency, and also audit quality